Water-soluble solder paste for semiconductor chip and preparation method of water-soluble solder paste

By optimizing the composition ratio and additives of water-soluble solder paste, the problem of insufficient performance of existing solder paste in semiconductor chip manufacturing is solved, and the high conductivity, thermal conductivity and bonding strength is improved, meeting the needs of environmental protection and high-precision manufacturing.

CN119794650AActive Publication Date: 2025-04-11JIANGSU BOLAN XIWEI METAL TECH CO LTD

Patent Information

Application Number
CN202411905675.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-11
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

The existing water-soluble solder paste has problems such as insufficient conductivity, thermal conductivity, bonding strength and storage stability in semiconductor chip manufacturing, and the lead-containing components of traditional solder materials are harmful to the environment and human health.

Method used

A high-performance water-soluble solder paste is prepared by optimizing the composition ratio of alloy powder, conductive adhesive and flux, and introducing specific additives. The solder paste contains high-purity tin powder, metal elements that improve thermal conductivity, polymer resins and conductive fillers. The flux contains organic acid chelating agents, surfactants, etc., and other additives such as antioxidants and thixotropic agents are used to improve storage stability and construction performance.

Benefits of technology

It significantly improves the electrical conductivity, thermal conductivity and bonding strength of solder paste, improves storage stability and construction performance, meets the needs of high-precision semiconductor manufacturing, and meets environmental protection requirements.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of semiconductor packaging materials, and particularly discloses a water-soluble solder paste for a semiconductor chip, and the solder paste comprises the following components by taking the total mass of the solder paste as 100%: 60-70% of alloy powder, the mass content of tin powder is not less than 37.8%, and the alloy powder contains metal elements for improving the heat-conducting property; the conductive adhesive is used for enhancing the conductivity and the bonding strength of the solder paste; the solder paste comprises the following components in percentage by weight: 20%-30% of soldering flux which comprises an organic acid chelating agent, a surfactant, a corrosion inhibitor, an organic solvent and deionized water and is used for promoting the welding process and reducing residues after welding, and 0%-5% of other additives which comprise an antioxidant, a thixotropic agent and a flatting agent and are used for improving the storage stability and construction performance of the solder paste. According to the water-soluble solder paste, the high-purity alloy powder is adopted, the mass content of the tin powder is not lower than 37.8%, metal elements for improving the heat conduction performance are introduced, and high heat conduction performance and low resistivity of a welding material are guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of semiconductor packaging materials, in particular to a water-soluble solder paste for a semiconductor chip and a preparation method thereof. Background Art

[0002] With the rapid development of electronic equipment and semiconductor technology, the performance requirements for welding materials are increasing. Especially in the process of semiconductor chip manufacturing, welding materials must not only have excellent electrical and thermal conductivity, but also good bonding strength and stability. Traditional welding materials such as tin-lead alloys are harmful to the environment and human health due to their lead content, and are gradually being replaced by environmentally friendly lead-free solders. Among them, water-soluble solder paste has become one of the research hotspots of lead-free solder due to its advantages such as environmental protection and easy cleaning.

[0003] Water-soluble solder paste in the prior art is usually composed of alloy powder, flux and adhesive. However, the common water-soluble solder paste on the market still has many shortcomings in practical applications. For example, the metal oxides in the alloy powder can easily reduce the welding effect, the residue of the flux is difficult to clean, and the bonding strength and conductivity of the conductive adhesive need to be improved. In addition, the storage stability and construction performance of the solder paste also need to be further improved to meet the needs of high-precision semiconductor manufacturing processes. Summary of the invention

[0004] The purpose of the present invention is to provide a water-soluble solder paste for semiconductor chips and a preparation method thereof. By optimizing the composition ratio of alloy powder, conductive adhesive and flux, and introducing specific additives, the water-soluble solder paste provided by the present invention not only has excellent electrical conductivity and thermal conductivity, but also significantly improves bonding strength and storage stability; at the same time, the improved preparation process ensures uniform dispersion of each component and good welding effect, meeting the needs of high-performance semiconductor chip manufacturing.

[0005] To achieve the above object, the present invention provides the following technical solution: a water-soluble solder paste for semiconductor chips, the total mass of which is 100%, and the components thereof include: Alloy powder: 60% to 70%, of which the mass content of tin powder is not less than 37.8%, and the alloy powder contains metal elements that improve thermal conductivity; Conductive adhesive: 10% to 15%, used to enhance the conductivity and bonding strength of solder paste; Flux: 20% to 30%, including organic acid chelating agent, surfactant, corrosion inhibitor, organic solvent and deionized water, used to promote the soldering process and reduce the residue after soldering. Other additives: 0% to 5%, including antioxidant, thixotropic agent and leveling agent, used to improve the storage stability and construction performance of solder paste.

[0006] Preferably, the mass content of tin powder in the alloy powder is 37.8% to 46.2%.

[0007] Preferably, the conductive adhesive is formed by mixing the following components in proportion: a polymer resin base material accounts for 60% to 70% of the total mass of the conductive adhesive, a conductive filler accounts for 20% to 30% of the total mass of the conductive adhesive, the conductive filler includes but is not limited to graphite, carbon nanotubes or metal nanoparticles, and an additive accounts for 5% to 10% of the total mass of the conductive adhesive, and the additive is used to improve the compatibility of the adhesive with the alloy powder and the flux, thereby further improving the conductivity and bonding strength of the solder paste.

[0008] Preferably, the organic acid chelating agent accounts for 10% to 15% of the total mass of the flux, and is used to react with metal surface oxides to form soluble salts to promote welding; the surfactant accounts for 5% to 10% of the total mass of the flux, and is used to improve the wettability of the welding liquid to the metal surface; the corrosion inhibitor accounts for 1% to 3% of the total mass of the flux to prevent metal corrosion during welding; the organic solvent accounts for 30% to 40% of the total mass of the flux, and is used as a solvent to dissolve the above components; and deionized water accounts for 20% to 30% of the total mass of the flux, and is used to adjust the viscosity and fluidity of the flux to ensure the smooth progress of the welding process.

[0009] A method for preparing water-soluble solder paste for semiconductor chips comprises the following steps: Step 1: Weigh the raw materials of alloy powder, conductive adhesive, flux and other additives according to the proportion; Step 2: uniformly mix the alloy powder and the conductive adhesive, and perform ball milling to obtain a mixed powder with uniform particle size distribution; Step 3: Mix the mixed powder obtained in step 2 with the components in the flux and other additives, and stir them thoroughly to make the components evenly dispersed; Step 4: Degas the evenly mixed materials to remove bubbles in the materials; Step 5: Grind or disperse the degassed material to obtain the final water-soluble solder paste.

[0010] Preferably, in step 2, the parameters of the ball milling process are as follows: Mixing time: 5-10 minutes, to ensure initial mixing; Ball mill speed: 200-300 rpm, adjusted according to the properties of the ball milling media and the mixture; Ball milling time: 2-4 hours, adjusted according to the required particle size distribution.

[0011] Preferably, in step 3, the stirring parameters are as follows: Stirring speed: Stir at medium speed to avoid generating too much heat that affects the properties of the material; Stirring time: 10-15 minutes, to ensure that all components of the flux are fully dispersed in the mixed powder; Mixing method: Mechanical mixing or planetary mixing to ensure uniform mixing.

[0012] Preferably, in step 3, the parameters of the degassing treatment are as follows: Degassing temperature: room temperature to slightly above room temperature, not exceeding 50°C, to avoid thermal decomposition of materials; Degassing time: 30 minutes to 1 hour, the specific time is determined according to the bubble content in the material and the degassing efficiency; Degassing method: vacuum degassing or degassing under nitrogen protection to reduce the oxidative effect of oxygen on the material.

[0013] The present invention provides a water-soluble solder paste for semiconductor chips and a preparation method thereof, which has the following beneficial effects: 1. The water-soluble solder paste of the present invention adopts high-purity alloy powder, wherein the mass content of tin powder is not less than 37.8%, and metal elements that improve thermal conductivity are introduced to ensure high thermal conductivity and low resistivity of the welding material; the conductive adhesive is composed of polymer resin, conductive filler (such as graphite, carbon nanotubes or metal nanoparticles) and specific additives, and the conductive performance and bonding strength of the solder paste are significantly improved by optimizing the ratio; the flux contains organic acid chelating agent, surfactant, corrosion inhibitor, organic solvent and deionized water, which effectively promotes the welding process and reduces the residue after welding, thereby improving the welding quality and cleaning efficiency.

[0014] 2. Through the preparation method of the present invention, the components of the solder paste are evenly dispersed, and the high quality and high performance of the final product are ensured through the process steps of ball milling, stirring, degassing, etc. The application of the water-soluble solder paste in the manufacture of semiconductor chips not only meets environmental protection requirements, but also significantly improves the reliability and accuracy of the welding process, and has broad application prospects. DETAILED DESCRIPTION

[0015] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0016] Example 1: Basic formula and preparation method: formula: Alloy powder: 65% (total mass), of which tin powder content is 42% (alloy powder mass), and the rest is alloy containing metal elements (such as copper and silver) that improve thermal conductivity; Conductive adhesive: 12%, composed of 65% polymer resin, 25% graphite as conductive filler and 10% additives (to improve compatibility); Flux: 23%, including 12% organic acid chelating agent, 7% surfactant, 2% corrosion inhibitor, 35% organic solvent and 25% deionized water; Other additives: 0%, no additional additives were added in this embodiment.

[0017] Preparation method: 1. Accurately weigh the raw materials of each component according to the above ratio; 2. Mix the alloy powder and the conductive adhesive and perform preliminary mixing for 5 minutes; 3. Use a ball mill at 250 rpm for 3 hours to obtain a mixed powder with uniform particle size distribution; 4. After the components of the flux are evenly mixed, mix them with the mixed powder obtained in step 3 and stir them mechanically at medium speed for 12 minutes to ensure that the components are fully dispersed; 5. Perform vacuum degassing at room temperature for 45 minutes to remove bubbles in the material; 6. The final product does not require additional grinding and can be directly packaged and stored.

[0018] Example 2: Optimizing thermal and electrical conductivity formula: Alloy powder: 68% (total mass), of which tin powder content is 46.2% (alloy powder mass), and 5% silver powder is added to the alloy to improve thermal conductivity; Conductive adhesive: 13%, composed of 68% polymer resin, 22% carbon nanotubes as conductive filler and 10% additives; Flux: 19%, including 14% organic acid chelating agent, 8% surfactant, 1.5% corrosion inhibitor, 35% organic solvent and 22.5% deionized water; Other additives: 0.8%, including antioxidants and thixotropic agents.

[0019] Preparation method: The steps of Example 1 were followed, but in step 2, the ball milling time was extended to 4 hours to ensure that the silver powder was fully dispersed; in step 3, the stirring time was adjusted to 15 minutes to ensure that the carbon nanotubes were evenly dispersed.

[0020] Example 3: Adjusting flux composition and degassing conditions formula: Alloy powder: 60% (total mass), of which tin powder content is 37.8% (alloy powder mass); Conductive adhesive: 10%, composed of 70% polymer resin, 25% metal nanoparticles as conductive filler and 5% additives; Flux: 30%, including 10% organic acid chelating agent, 5% surfactant, 3% corrosion inhibitor, 35% organic solvent and 27% deionized water; Other additives: 5%, including antioxidants, thixotropic agents and leveling agents.

[0021] Preparation method: 1. Weigh each component according to the proportion; 2. The alloy powder and the conductive adhesive are mixed and ball-milled as in Example 1, but the ball-milling time is adjusted to 2.5 hours; 3. After the flux is evenly mixed, mix it with the mixed powder and stir it at medium speed for 10 minutes using a planetary mixer; 4. The degassing treatment is carried out under nitrogen protection at a temperature slightly higher than room temperature (45°C) for 1 hour to ensure that bubbles are completely removed and oxidation is reduced; 5. After degassing, it can be packaged directly without additional grinding.

[0022] The three embodiments demonstrate the adjustment of different formulations and preparation conditions, aiming to optimize the performance of water-soluble solder paste for semiconductor chips. By adjusting the alloy powder composition, conductive adhesive formulation, flux component ratio and preparation process parameters, solder paste products that meet different application requirements can be obtained.

[0023] Flux performance evaluation parameters and data table: Example Thermal conductivity (W / m·K) Volume resistivity (Ω·cm) Wetting time(s) Bubble content (ppm) Stability test (days) 1 X1 = 0.5 Y1 = 1000 Z1 = 15 A1 = 100 B1 = 90 2 X2 = 0.8 Y2 = 800 Z2 = 12 A2 = 80 B2 = 120 3 X3 = 0.6 Y3 = 900 Z3 = 14 A3 = 60 B3 = 100 Thermal conductivity: The thermal conductivity of Example 2 (X2=0.8) is higher than that of Example 1 (X1=0.5), which is in line with the expectation of adding high thermal conductivity silver powder. Although the alloy powder content of Example 3 (X3=0.6) is reduced, the thermal conductivity is still between X1 and X2, which shows the effect of formula changes on thermal conductivity.

[0024] Volume resistivity: After using carbon nanotubes in Example 2, the volume resistivity (Y2=800) is significantly reduced, showing better conductivity; the resistivity of Example 3 (Y3=900) is between Y1 and Y2, indicating that metal nanoparticles have a certain contribution to conductivity, but not as significant as carbon nanotubes.

[0025] Wetting time: The wetting time is affected by many factors. The wetting time of Example 2 (Z2=12s) is slightly shorter than that of Example 1 (Z1=15s), which may be due to the improvement of the formula. The wetting time of Example 3 (Z3=14s) is between the two.

[0026] Bubble content: Example 3 adopts more optimal vacuum degassing treatment conditions, so the bubble content (A3=60ppm) is the lowest, while the bubble content of Example 1 (A1=100ppm) and Example 2 (A2=80ppm) is relatively high.

[0027] Stability test: The stability test results showed that the flux of Example 2 (B2=120 days) performed best under specific storage conditions, followed by Example 3 (B3=100 days) and Example 1 (B1=90 days).

[0028] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A water-soluble solder paste for semiconductor chips, characterized in that: Taking the total mass of the solder paste as 100%, the components thereof include: Alloy powder: 60% to 70%, of which the mass content of tin powder is not less than 37.8%, and the alloy powder contains metal elements that improve thermal conductivity; Conductive adhesive: 10% to 15%, used to enhance the conductivity and bonding strength of solder paste; Flux: 20% to 30%, including organic acid chelating agent, surfactant, corrosion inhibitor, organic solvent and deionized water, used to promote the soldering process and reduce the residue after soldering. Other additives: 0% to 5%, including antioxidant, thixotropic agent and leveling agent, used to improve the storage stability and construction performance of solder paste.

2. A water-soluble solder paste for semiconductor chips according to claim 1, characterized in that: The mass content of tin powder in the alloy powder is 37.8% to 46.2%.

3. A water-soluble solder paste for semiconductor chips and a preparation method thereof according to claim 2, characterized in that: The conductive adhesive is formed by mixing the following components in proportion: a polymer resin base material accounts for 60% to 70% of the total mass of the conductive adhesive, a conductive filler accounts for 20% to 30% of the total mass of the conductive adhesive, the conductive filler includes but is not limited to graphite, carbon nanotubes or metal nanoparticles, and an additive accounts for 5% to 10% of the total mass of the conductive adhesive, and the additive is used to improve the compatibility of the adhesive with the alloy powder and the flux, thereby further improving the conductive performance and bonding strength of the solder paste.

4. A water-soluble solder paste for semiconductor chips and a preparation method thereof according to claim 3, characterized in that: The organic acid chelating agent accounts for 10% to 15% of the total mass of the flux and is used to react with the oxide on the metal surface to form soluble salts to promote welding; the surfactant accounts for 5% to 10% of the total mass of the flux and is used to improve the wettability of the welding liquid to the metal surface; the corrosion inhibitor accounts for 1% to 3% of the total mass of the flux to prevent the corrosion of the metal during the welding process; the organic solvent accounts for 30% to 40% of the total mass of the flux and is used as a solvent to dissolve the above components; and the deionized water accounts for 20% to 30% of the total mass of the flux and is used to adjust the viscosity and fluidity of the flux to ensure the smooth progress of the welding process.

5. The method for preparing a water-soluble solder paste for a semiconductor chip according to claim 4, characterized in that: The following steps are involved: Step 1: Weigh the raw materials of alloy powder, conductive adhesive, flux and other additives according to the proportion; Step 2: uniformly mix the alloy powder and the conductive adhesive, and perform ball milling to obtain a mixed powder with uniform particle size distribution; Step 3: Mix the mixed powder obtained in step 2 with the components in the flux and other additives, and stir them thoroughly to make the components evenly dispersed; Step 4: Degas the evenly mixed materials to remove bubbles in the materials; Step 5: Grind or disperse the degassed material to obtain the final water-soluble solder paste.

6. The method for preparing a water-soluble solder paste for a semiconductor chip according to claim 5, characterized in that: In step 2, the parameters of the ball milling process are as follows: Mixing time: 5-10 minutes, to ensure initial mixing; Ball mill speed: 200-300 rpm, adjusted according to the properties of the ball milling media and the mixture; Ball milling time: 2-4 hours, adjusted according to the required particle size distribution.

7. The method for preparing a water-soluble solder paste for a semiconductor chip according to claim 6, characterized in that: In step 3, the stirring parameters are as follows: Stirring speed: Stir at medium speed to avoid generating too much heat that affects the properties of the material; Stirring time: 10-15 minutes, to ensure that all components of the flux are fully dispersed in the mixed powder; Mixing method: Mechanical mixing or planetary mixing to ensure uniform mixing.

8. The method for preparing a water-soluble solder paste for a semiconductor chip according to claim 7, characterized in that: In step 3, the parameters of the degassing treatment are as follows: Degassing temperature: room temperature to slightly above room temperature, not exceeding 50°C, to avoid thermal decomposition of materials; Degassing time: 30 minutes to 1 hour, the specific time is determined according to the bubble content in the material and the degassing efficiency; Degassing method: vacuum degassing or degassing under nitrogen protection to reduce the oxidative effect of oxygen on the material.

Citation Information

Patent Citations

  • Solder paste and preparation method thereof

    CN103170757A

  • Environment-friendly and low-temperature residue-free solder paste and preparing method thereof

    CN107088716A

  • Solder alloy and solder paste comprising same

    CN114340836A

  • A water-soluble die-bonding solder paste for high-power LED packaging and its preparation method

    CN114932335A

  • Low-temperature curing conductive adhesive, preparation method thereof and transparent display screen

    CN117050686A

Cited By

  • Water-soluble soldering paste and preparation method thereof

    CN121870336A